Associations between psychosocial risk factors, and changes in substance dependence and psychosocial functioning, during engagement with digital cognitive behavioral therapy for methamphetamine use: use of 'Breaking Free from Substance Abuse' by incarcerated people during the COVID-19 pandemic - Sarah Elison-Davies; Jamie Newsome; Andrew Jones; Glyn Davies; Jonathan Ward (Health & Justice, 2022)
Abstract Background Methamphetamine use can be associated with involvement with correctional services and incarceration. Traditionally, treatments for methamphetamine use have been delivered in-person – however, lockdowns initiated during the COVID-19 pandemic significantly reduced access to such in-person support in prisons. Therefore, in May 2020 a digital cognitive-behavioral therapy (CBT) program for substance use disorders - 'Breaking Free from Substance Abuse' - was made available across prisons in Ohio in order to meet this treatment gap. This represents the first time this digital CBT intervention has been made widely available to incarcerated people residing in prisons or jails in the United States (US). This was a within-subjects study using data from 2187 Ohio prison residents who engaged with this digital CBT program to address their methamphetamine use. Results Participants reported multiple psychosocial risk factors, including moderate to severe substance dependence, depression and anxiety; interpersonal conflict; aggressive behavior; paranoia; and difficulties with work, education and accommodation. Significant reductions in substance dependence, depression/anxiety and biopsychosocial impairment, and improvements in quality of life, were identified in the sample. Risk factors were associated with less positive outcomes, specifically interpersonal conflict and poor mental health. Completion of specific components of the program were associated with more positive outcomes – a dose response was also identified. Conclusions Digital CBT can be delivered in secure US correctional settings and may help to fill unmet needs for in-person treatment. Specifically, this digital CBT program may support incarcerated individuals to address methamphetamine use, with outcomes being associated with psychosocial risk factors and program engagement.